Searle's Theory: The Effect of Illocution Speech Act in Tinder Dating Apps - Dilia Dewi, Ni Putu; Irwandika, Gede (e-Journal of Linguistics; Vol 18 No 2 (2024): ejl-JulyDO - 10.24843/ling.2023.v30.i02.p13, 2024)
This study presents a novel concept that correctly chosen speech acts can guide communication in the desired direction without offending or damaging each other. Because communication serves as a bridge between facts and sentiments, this study's novelty may assist Tinder users in achieving their aim of finding a life partner. Users of the Tinder dating application also have the desire to locate a companion by playing this app. The speech act utilized serves as a criterion for the conversation's success. The goal of this study is to categorize the many forms of illocutionary phrases used by Tinder users, as well as how speech acts affect the maintenance of relationships. As a result, this research approach is qualitative descriptive research, as the data used is Tinder users' speech acts in establishing communication. Data was collected from a sample of 15 Tinder users by direct observation and reading their discussions with members of the opposite sex. The data was then divided into five sorts of illocutionary speech acts based on Shearly's Theory: directive, expressive, representational, declaration, and commissive. The following analytical data was collected through direct interviews with Tinder users, who provided reasons for employing these speech actions in their effective conversation. Data is given in narrative and qualitative descriptive formats.